Polycomb Repressive Complex 2-Dependent and -Independent Functions of Jarid2 in Transcriptional Regulation in Drosophila - Herz, Hans-Martin (American Society for Microbiology, 2012)
Jarid2 was recently identified as an important component of the mammalian Polycomb repressive complex 2 (PRC2), where it has a major effect on PRC2 recruitment in mouse embryonic stem cells. Although Jarid2 is conserved in Drosophila, it has not previously been implicated in Polycomb (Pc) regulation. Therefore, we purified Drosophila Jarid2 and its associated proteins and found that Jarid2 associates with all of the known canonical PRC2 components, demonstrating a conserved physical interaction with PRC2 in flies and mammals. Furthermore, in vivo studies with Jarid2 mutants in flies demonstrate that among several histone modifications tested, only methylation of histone 3 at K27 (H3K27), the mark implemented by PRC2, was affected. Genome-wide profiling of Jarid2, Su(z)12 (Suppressor of zeste 12), and H3K27me3 occupancy by chromatin immunoprecipitation with sequencing (ChIP-seq) indicates that Jarid2 and Su(z)12 have very similar distribution patterns on chromatin. However, Jarid2 and Su(z)12 occupancy levels at some genes are significantly different, with Jarid2 being present at relatively low levels at many Pc response elements (PREs) of certain Homeobox (Hox) genes, providing a rationale for why Jarid2 was never identified in Pc screens. Gene expression analyses show that Jarid2 and E(z) (Enhancer of zeste, a canonical PRC2 component) are not only required for transcriptional repression but might also function in active transcription. Identification of Jarid2 as a conserved PRC2 interactor in flies provides an opportunity to begin to probe some of its novel functions in Drosophila development.